Pharmacological Treatment of Tachyarrhythmias in Acute Myocardial Infarction - a Review - Alexandru DEACONU; Silvia DEACONU; Andrei RADU; Maria DOROBANTU (Sciendo, 2021)
Acute myocardial infarction (AMI) causes severe metabolic and electrophysiological changes that induce silent or symptomatic life-threatening arrhythmias. Ventricular arrhythmias and atrial fibrillation are common during the early phase of AMI and are also important prognostic factors. Rapid identification and treatment of these arrhythmias can be life-saving, since in-hospital mortality rises dramatically in patients who develop arrhythmias with a fast ventricular rate following an AMI. Along with myocardial revascularization, adequate pharmacological therapy of hemodynamically relevant arrhythmias is generally useful. Since there are no controlled randomized trials comparing different antiarrhythmic drugs (AADs) in AMI, optimal decision making is based on medical societies guidelines recommendations and clinical judgement.